Tracheobronchial Involvement of Rosai–Dorfman Disease: Case Report and Review of the Literature. Issue 7 (February 2016) - Boissière, Louis; Patey, Martine; Toubas, Olivier; Vella-Boucaud, Juliette; Perotin-Collard, Jeanne-Marie; Deslée, Gaëtan; Lebargy, Francois; Dury, Sandra
Abstract : Abstract: Rosai–Dorfman Disease (RDD) is a rare non-neoplastic entity, also known as sinus histiocytosis with massive lymphadenopathy (SHML), characterized by a benign proliferation of histiocytes in lymph nodes. Localized forms of RDD involving the tracheobronchial tree are very rare. There is no consensus regarding the management of central airway forms and recurrence is frequent. We report the case of an 81-year-old Caucasian woman admitted in 2014 for chronic cough. Her main medical past history included a diagnosis of sinonasal RDD in 1996 with recurrent obstructive rhinosinusitis requiring repeated sinonasal surgery, and a diagnosis of tracheal RDD in 2010 with 2 asymptomatic smooth lesions (5 and 7 mm) on the anterior tracheal wall. Physical examination was normal in 2014. Pulmonary function tests showed an obstructive pattern. Computed tomographic scan revealed a mass arising from the anterior wall of the trachea that projects into the tracheal lumen. Fiberoptic bronchoscopy showed a hypervascular multilobular lesion (2 cm) arising from the anterior tracheal wall and causing 50% obstruction of the tracheal lumen. Mechanical resection with electrocoagulation of the tracheal mass was performed by rigid bronchoscopy with no complication. Histological examination demonstrated tracheal RDD. One year after endotracheal resection, the patient presented no recurrence of cough and the obstructive pattern had resolved. Reports on tracheobronchial involvement are scarce. Symptomatic tracheobronchial obstruction requires mechanical resection by rigid bronchoscopy or surgery. Recurrence is frequent, justifying long-term follow-up.